The Messiness of Ethics in Education - Cliffe, Johanna; Solvason, Carla (Journal of Academic Ethics, 2022)
This article considers the multifaceted concept of ethics and how, despite being a familiar notion within education, it is still much contested within literature and professional practice. Drawing on postmodern, feminist and political literature, the authors explore (re)conceptualisations of ethics and ethicality in relation to ethical identity, professionalism and practice. Applying philosophical and metaphorical tools, such as the rhizome and nomad (Deleuze and Guattari, 1987), the authors suggest there is the potential to accommodate the multiple and often divergent facets of ethics, thereby engaging with different ethical possibilities. It is argued that the propensity for reducing ethics to merely procedural protocols and guidelines marginalises the richness of ethics and, all too frequently, leaves practitioners ill-equipped to navigate the reality of day-to-day ethics.